TaPro (TaskProgress) ; A System To Monitor Progress of Students’ Task - ANDALINA DAYANG, MADANG (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Nowadays, task monitoring progress for team have become a medium for organizations to manage their workloads in team and organize the team as well as works systematically. The methods or approach to monitor task progress used by individuals are different and various. However, for some who may not know about this task monitoring system, they are still using the traditional ways such as text messaging their friends and asking around about the members progress and the leader might not know what is the progress of each members only in verbally without rigid proof. Therefore, TaPro (Task Progress); A System to Monitor Progress of Students’ Task System, allows students to monitor their members progress as well as to avoid “free-rider” in the group. Apart from that, the aim of this project is to develop a web-based system where students can monitor their members task progress as well as organize the team systematically and distribute the workloads equally. According to the literature review, there are three existing applications that are similar to the concept of this proposed system. The methodology used to develop this proposed system is Waterfall model. A questionnaire had been created in Google Forms and shared through media social for UNIMAS students from different faculty to answer to get the requirements to develop and design the proposed system. The proposed system is developed based on the collected requirements and design. The testing such as unit testing, functionality testing and user testing are carried out. Based on the user testing, the proposed system is working well. Last but not least, the conclusion and the future work are discussed to improve this system.